Respuesta :

Answer:

see explanation

Step-by-step explanation:

Given the 2 equations

2r + 3s = - 5 → (1)

6s = 2r → (2) ( divide both sides by 2 ), then

r = 3s

Substitute r = 3s into (1)

2(3s) + 3s = - 5

6s + 3s = - 5

9s = - 5 ( divide both sides by 9 )

s = - [tex]\frac{5}{9}[/tex]

Substitute this value into either of the 2 equations and evaluate for r

Substituting into r = 3s, then

r = 3 × - [tex]\frac{5}{9}[/tex] = - [tex]\frac{5}{3}[/tex]

Solution is r = - [tex]\frac{5}{3}[/tex] and s = - [tex]\frac{5}{9}[/tex]